The Impact of the Shale Oil Revolution on U.S. Oil and Gasoline Prices - Lutz Kilian (Center for Economic Studies and ifo Institute (CESifo), 2016)
This article examines how the shale oil revolution has shaped the evolution of U.S. crude oil and gasoline prices. It puts the evolution of shale oil production into historical perspective, highlights uncertainties about future shale oil production, and cautions against the view that the U.S. may become the next Saudi Arabia. It then reviews the effects of the ban on U.S. crude oil exports, of capacity constraints in refining and transporting crude oil, of differences in the quality of conventional and unconventional crude oil, and of the recent regional fragmentation of the global market for crude oil on the determination of U.S. oil and gasoline prices. It discusses the reasons for the persistent wedge between U.S. crude oil prices and global crude oil prices in recent years and for the fact that domestic oil prices below global levels have not translated to lower U.S. gasoline prices. It also examines the role of shale oil in causing the 2014 oil price decline. Finally, it explains why the shale oil revolution unlike the shale gas revolution is unlikely to stimulate a U.S. boom in oil-intensive manufacturing industries, and it explores more generally the implications of the shale oil revolution for the U.S. economy.
Keywords: Q43; 330; shale oil; unconventional oil; tight oil; infrastructure; export ban; refining; U.S. oil independence; oil sands; capacity constraints; oil trade